Laura Spess Jackson letter to Thomas H. Kent regarding bird sightings, June 5, 1992 - Jackson, Laura Spesset al (1992)
Field notes contributed by Laura Spess Jackson in a letter to Thomas H. Kent including reports from other observers. This item was submitted past the deadline for the Iowa Ornithologists' Union Quarterly Report of spring 1992. Plustek - flatbed